LAW AS A VALUE, VALUES IN LAW (PART TWO) - Baikovs, Aleksandrs (Administrative and Criminal Justice, 2021)
The paper deals with the category of "values", the Rights as a value, and fundamental values of law; including freedom, justice, and equality have been analyzed.The relevance of the research is determined not only by the apparent lack of exploration of the problem but also by the fact that the value of rights and legal values determine direction and meaning, as well as the content of the rules of law, which is their normative expression, and, ultimately, appearing as a kind of basis for the legal culture, the source of the formation of the legal consciousness and establishing legal order, ensuring the efficiency of legal regulation due to the using the embodiment in reality of freedom, justice, equality.Legal norms themselves acquire the importance of values and become the subject of evaluation. Among values themselves, which act as an ideal justification of law rules, the law rules themselves and assessments, on the one hand, there are not only close ties but also mutual transitions. Therefore, both their interrelated explanations and differentiation are necessary.